Audit: legal aspects in a pandemic - Олюха, Віталій Григорійович; Олюха, В. Г.; Олюха, Виталий Григорьевич; Oliukha, Vitalii H.; Olyukha, Vitalіі; Добровольська, Володимира Володимирівна; Добровольська, В. В.; Добровольская, Владимира Владимировна; Dobrovolska, Volodymyra V.; Dobrovolska, Vladimira; Чайковська, Валентина Володимирівна; Чайковська, В. В.; et al. (Los Hemisferios University, 2020)
This article is devoted to changes in the economic and legal conditions of audit activity in the context of a pandemic and its consequences. It will be useful both to top managers of companies and to audit companies and their specialists. The object of the research is public relations in the field of auditing. The interests of the three main parties are distinguished separately: states, business and auditing companies. The work has the following structure: world experience in auditing during a pandemic; national legal framework for auditing: problems and solutions; the current state of the audit services market: problems and solutions; recommendations to the participants of the audit market. The research methodology is based on general and special scientific methods, in particular: historical-legal, formal-legal, comparative analysis, and modeling. The study concludes that it is the audit system that still acts as a locomotive for the business environment, since an audit is at the forefront of the latest technological solutions (processing Big Data, leveling information asymmetry), is able to quickly work with financial and economic reporting data and propose appropriate measures. However, for this, the business should not be afraid to change in the wake of this new changing world, and audit companies should quickly adapt to new trends and needs.

Ця стаття присвячена змінам економічних та правових умов аудиторської діяльності в умовах пандемії та її наслідків. Вона буде корисною як топ-менеджерам компаній, так і аудиторським компаніям та їх спеціалістам. Об’єкт дослідження – зв’язки з громадськістю у сфері аудиту. Окремо виділяються інтереси трьох основних сторін: держави, бізнесу та аудиторських компаній. Робота має таку структуру: світовий досвід аудиту під час пандемії; національна правова база аудиту: проблеми та шляхи вирішення; сучасний стан ринку аудиторських послуг: проблеми та шляхи вирішення; рекомендації учасникам аудиторського ринку. Методологія дослідження базується на загальнонаукових і спеціально-наукових методах, зокрема: історико-правовому, формально-правовому, порівняльному аналізі та моделюванні. У дослідженні робиться висновок, що саме система аудиту як і раніше виступає локомотивом бізнес-середовища, оскільки аудит стоїть у перших рядах новітніх технологічних рішень (обробка великих даних, нівелювання асиметрії інформації), здатен швидко працювати з фінансовими та даними економічної звітності та запропонувати відповідні заходи. Однак для цього бізнес не повинен боятися змінюватися на хвилі цього нового мінливого світу, а аудиторські компанії повинні швидко адаптуватися до нових тенденцій і потреб.
Olyukha V. Audit: legal aspects in a pandemic / V. Olyukha, V. Dobrovolska, V. Chaikovska, V. Popeliuk, J. Dyshkantiuk // Ius Humani. Law Journal. - Vol. 9. - Issue 2. - Los Hemisferios University, 2020. - P. 365-388.
Keywords: audit; audit services; International Auditing Standards; financial reporting; pandemic; аудит; аудиторські послуги; міжнародні стандарти аудиту; фінансова звітність; пандемія; Research Subject Categories::LAW/JURISPRUDENCE